2007
DOI: 10.1002/mrd.20696
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of human granulosa lutein cells after hCG or LH stimulation in a spheroidal cell culture system

Abstract: The growth and development of the corpus luteum (CL) is regulated by gonadotropic hormones. It is formed by granulosa cells (GCs), theca cells, and endothelial cells, and is the primary source of circulating progesterone. During early pregnancy only human chorionic gonadotropin (hCG) but not luteinizing hormone (LH) extends the life span of the CL, although hCG and LH interact with the same receptor and have similar actions on the CL. In this study a recently by our group established spheroidal GC culture assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…A modulatory effect on cell viability and function by co-culturing different cell types was shown by Lancaster et al, for stem cell based organoid models [ 16 ]. In addition, a form of self-organization of granulosa cells and different other cells has already been described by Qiu et al [ 17 ] as well as our group [ 18 , 19 ]. De Souza and colleagues have shown that mesenchymal stem cells (MSC) increase viability and hormone production capacity of islets cells [ 20 ] and Jiang and colleagues reported a regulatory effect by endothelial cells on microglial cells [ 21 ].…”
Section: Discussionsupporting
confidence: 59%
“…A modulatory effect on cell viability and function by co-culturing different cell types was shown by Lancaster et al, for stem cell based organoid models [ 16 ]. In addition, a form of self-organization of granulosa cells and different other cells has already been described by Qiu et al [ 17 ] as well as our group [ 18 , 19 ]. De Souza and colleagues have shown that mesenchymal stem cells (MSC) increase viability and hormone production capacity of islets cells [ 20 ] and Jiang and colleagues reported a regulatory effect by endothelial cells on microglial cells [ 21 ].…”
Section: Discussionsupporting
confidence: 59%
“…Nonetheless, despite the usual major interest in the oocyte itself, ovarian tissue consists of many different cells which include granulosa, endothelial, and stroma cells. These are essential for ovarian function, since they are a source of hormones and since they nourish the growing oocyte, first and foremost the granulosa cells (Becker et al 2007 ; McKenzie et al 2004 ). Furthermore, angiogenesis begins within the stroma during early development of the follicles (Suzuki et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, initial studies on primate granulosa cells [86] did not support the concept of differential receptor activation by hCG and hLH, based on the kinetics of progesterone production. Elegant studies using human cell systems recently identified differences in the potency and chronic actions of LH and CG to stimulate cyclic AMP and progesterone secretion, plus the activation of cell signaling pathways [87, 88]. For example, LH was more potent in ERK and AKT activation to promote cell proliferation and survival, whereas hCG was more potent in cyclic AMP and steroid production.…”
Section: Extension Of Luteal Structure-function In Early Pregnancymentioning
confidence: 99%